A review: Independent water and wastewater treatment methods - Yusairah W.N.; Zawawi M.H.; Abidin S.Z.; Ismail I.N.; Zahari M.N.; Kamaruddin M.A.; Sidek L.M. (American Institute of Physics Inc., 2023)
The purpose of this paper is to present examples of independent water and wastewater treatment methods in a way to provide clean water to the community. Out there, tons of method exists to reduce the effect of the water pollutant and improve the water quality problems. In order to reduce the water problems, this paper focuses on the process of water and wastewater treatment by using three different methods which are natural and independent water and wastewater treatment, independent artificial water, and wastewater treatment and hybrid water and wastewater treatment. Natural independent method mostly using vegetation as a medium or mechanism to purify water. For the hybrid method, green energy artificial floating island(GAFI), solar power artificial floating Island (SAFI) and solar power lake and pond aeration system were studied the removal efficiency by all the devices. The methods were reviewed in order to find the efficiencies and effectiveness of each method. 2019 Author(s).